On One Class of Separable Dedekind Groups - Odintsova, O.O. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
We describe locally solvable groups G such that all their infinite subgroups that do not belong to a certain proper subgroup of the group under consideration are normal.